2014
DOI: 10.1007/s10802-013-9847-4
|View full text |Cite
|
Sign up to set email alerts
|

Teacher Characteristics and Peer Victimization in Elementary Schools: A Classroom-Level Perspective

Abstract: The purpose of this study was to investigate whether there is an association between teacher characteristics and peer victimization in elementary schools. We used data of 3,385 elementary school students (M age = 9.8) and 139 of their teachers (M age = 43.9) and employed Poisson regression analyses to explain the classroom victimization rate. Results showed a higher victimization rate in the classrooms of teachers who attributed bullying to external factors-factors outside of their control. In addition, the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
62
0
7

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 81 publications
(72 citation statements)
references
References 37 publications
3
62
0
7
Order By: Relevance
“…Accordingly, in these classrooms students would be more likely to perceive classmates who are victimized sometimes as victimized. These findings are in line with other studies in which the bullying process has been found to be strongly influenced by the classroom context (e.g., Oldenburg et al, 2015;Pozzoli, Gini, & Vieno, 2012;Salmivalli et al, 1996). Future studies could further investigate the relationship between classroom climate and reporter-receiver agreement.…”
Section: Classroom Characteristicssupporting
confidence: 90%
“…Accordingly, in these classrooms students would be more likely to perceive classmates who are victimized sometimes as victimized. These findings are in line with other studies in which the bullying process has been found to be strongly influenced by the classroom context (e.g., Oldenburg et al, 2015;Pozzoli, Gini, & Vieno, 2012;Salmivalli et al, 1996). Future studies could further investigate the relationship between classroom climate and reporter-receiver agreement.…”
Section: Classroom Characteristicssupporting
confidence: 90%
“…Their attitudes and intervention behavior influences pupils' bullying experiences (Saarento et al, ; Troop‐Gordon & Ladd, ), mediates the success of antibullying programs (Saarento, Boulton, & Salmivalli, ), and contributes to the stability or instability of victimization in the classroom in any given year (Serdiouk, Rodkin, Madill, Logis, & Gest, ). In their responses to bullying episodes among students, teachers function as role models (Oldenburg et al, ). At the same time, their interventions can clearly signal that bullying is not acceptable in school (e.g., Oldenburg et al, ; Saarento, Garandeau, & Salmivalli, ; Veenstra, Lindenberg, Huitsing, Sainio, & Salmivalli, ).…”
Section: The Role Of Teachers In Bullying Interventionsmentioning
confidence: 99%
“…In their responses to bullying episodes among students, teachers function as role models (Oldenburg et al, ). At the same time, their interventions can clearly signal that bullying is not acceptable in school (e.g., Oldenburg et al, ; Saarento, Garandeau, & Salmivalli, ; Veenstra, Lindenberg, Huitsing, Sainio, & Salmivalli, ).…”
Section: The Role Of Teachers In Bullying Interventionsmentioning
confidence: 99%
“…The role that teachers play in actively reducing bullying is influenced both by their perceptions of the problem of bullying in their schools (e.g., Holt & Keyes, 2004) as well as their perceptions of the overall school climate. For example, a recent study (Oldenburg et al, 2014) showed that higher victimization rates in classrooms are associated with a greater tendency among teachers to attribute the cause of the bullying to factors outside of their control and, consequently, to feel less confident about their abilities to intervene in bullying. Espelage and colleagues (2014) reported that staff and teachers’ commitment to prevent bullying was associated with less bullying, fighting and peer victimization.…”
Section: School Safety: Teachers’ Perspectivesmentioning
confidence: 99%